Sociality in the common mole-rat, Cryptomys hottentotus hottentotus : the effects of aridity - Spinks, Andrew Charles (Department of Biological Sciences, 2017)
This study addresses the extrinsic factors which have shaped the evolution and maintenance of sociality in the African mole-rats. Specifically, the common mole-rat was used as a model to assess the Aridity Food-Distribution Hypothesis (AFDH), as an explanation for the evolution of bathyergid sociality. The AFDH correlates mole-rat sociality with habitat aridity and the pattern of food distribution. Aspects relating to ecological constraints, foraging behaviour, population demography, reproductive biology and aggressive behaviour were compared between an arid and a mesic population of C. h. hottentotus, to assess how inter-habitat divergence in ecological attributes has influenced social behaviour within these two populations. In evaluating the AFDH as an explanation for the evolution of sociality within C. h. · hottentotus two broad questions were addressed: (1) do the assumptions of the AFDH hold true i.e. do arid and mesic habitats exhibit ecological differences, specifically with regard to the pattern of resource dispersion and the energetic costs of foraging, which influence foraging risks and consequently the costs of dispersal? and (2) do these inter-habitat differences have implications for bathyergid social evolution i.e. do the common mole-rat populations inhabiting arid and mesic areas exhibit regional differentiation in social behaviour? Substantial inter-site divergence in ecological characteristics, notably climate and resource attributes, were revealed in this study. Rainfall at the arid site was markedly lower and more sporadic, and evaporation levels significantly higher, than at the mesic site. Moreover, thermal constraints were more limiting at the arid site. These features will greatly elevate the costs of soil excavation and the risks of hyperthermia, severely restricting the occurrence of suitable burrowing opportunities at the arid locality. Consequently, foraging will be severely constrained in this area. At the mesic site, higher, more predictable rainfall, low evaporation rates and reduced thermal constraints will translate into more suitable burrowing opportunities for much, if not all, of the year. Regional differentiation in food resource characteristics was also evident. Although geophytes were clumped at both study localities, the density of geophytes was lower and the distance between geophytes or geophyte clumps concomitantly greater at the arid relative to the mesic site. Differences in resource dispersion in turn influenced the patterns of foraging. In response to the low geophyte density and associated longer foraging distances, burrow systems were notably longer and more linear at the arid site. Furthermore, food storage and in situ harvesting were essential components of cooperative foraging in C. h. hottentotus as they minimised the risks of starvation, particularly in arid habitats. Thus, resource characteristics together with the climatic restrictions on burrowing in arid areas may have a marked impact on foraging behaviour, imposing severe constraints on the mole-rats occurring there and ultimately shaping their foraging responses. Together, these factors satisfactorily account for the underlying premise of the AFDH, that arid and mesic habitats exhibit ecological differences with regard to the pattern of resource dispersion and the energetic costs of foraging, which are likely to influence foraging risks and the costs of dispersal. In evaluating the AFDH, the second question which needed to be addressed was whether the study populations exhibited divergence in their social behaviour. The populations revealed no differences in absolute group size or in reproductive characteristics which were related to the effects of aridity per se. However, distinct inter-population divergence was readily apparent in phenotypically plastic traits such as dispersal behaviour and xenophobia. Clear differences were evident between the arid and mesic sites in both the quantitative and qualitative nature of dispersal; dispersal was markedly constrained at the arid site and colonies demonstrated greater temporal stability, with more predictable temporal group membership. The ecological constraints on successful foraging at the arid site will curb opportunities for dispersal and promote cooperation in the C. h. hottentotus occurring there. Colony members should therefore maximise their inclusive fitness by natal philopatry, delayed dispersal and cooperative foraging. Inter-site differences were also apparent in the response of colony members to foreign conspecifics. Common mole-rats from the arid site were markedly more xenophobic than those from the mesic site, and aggressively rejected foreigners. For arid-occurring populations, the fitness penalties for failing to exclude foreigners from the colony burrow system and associated resources, will be more severe than for mesic-occurring populations, resulting in heightened levels of xenophobia. Again, colony cohesion and cooperation in arid areas are essential to individual survival and inclusive fitness. The regional differences in dispersal patterns and xenophobia revealed in this investigation may reflect adaptive variation in social behaviour between the study populations, and the results suggest that delayed dispersal and cooperation may be more crucial to individual survival in arid than in mesic areas. As such these findings provide support for the underlying contention of the AFDH that ecological constraints on foraging in arid areas have promoted a greater degree of social elaboration in mole-rats occurring there. This study provides persuasive support for the AFDH as an explanation for the adaptive significance of social behaviour and cooperation in the common mole-rat, and together with other investigations, suggests that the AFDH provides a valid explanation for the evolution of group-living in the Bathyergidae.